2004
DOI: 10.1089/lap.2004.14.201
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Assisted Colectomies in Kidney Transplant Recipients with Colon Cancer

Abstract: The benefits of minimal access surgery seem to be shared by kidney transplant recipients. A key feature may be to avoid stopping immunosuppression perioperatively, therefore lowering the potential risk of rejection. Also, lessening the number of wound-related problems appears important for these patients. LAC in experienced hands must be considered a safe alternative for elective colon resections in highly selected patients with kidney transplants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…In addition, 14 lymph nodes were harvested, which fulfilled the standard of radical operation. Similar outcomes could be achieved by Rivas [ 8 ] during the laparoscopic resection for colon cancer in transplant patients, as long as the allograft was placed in the contralateral side of the colon resection. As for disease-free survival and overall survival, our patient was alive without recurrence and metastasis after 4 months of follow-up.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In addition, 14 lymph nodes were harvested, which fulfilled the standard of radical operation. Similar outcomes could be achieved by Rivas [ 8 ] during the laparoscopic resection for colon cancer in transplant patients, as long as the allograft was placed in the contralateral side of the colon resection. As for disease-free survival and overall survival, our patient was alive without recurrence and metastasis after 4 months of follow-up.…”
Section: Discussionmentioning
confidence: 55%
“…[ 6 , 7 ] Conventional surgical treatment for CRC represents a great risk to these high-risk patients, and the benefits of minimal access surgery seem to be shared by them. [ 8 ] However, there is still some lack of literature about the evaluation on outcome of laparoscopic surgery for CRC in patients after organ transplantation. Herein, we report a case of a patient who presented with advanced rectal cancer 4 years after kidney transplantation, and underwent laparoscopic assisted low anterior resection.…”
Section: Introductionmentioning
confidence: 99%
“…Reshef et al reported the results of 37 solid organ transplant recipients after emergency surgery of the colon and found a renal failure in four patients (vs. one patient in non-transplanted control group) [12]. Contrary to that, Kaluza et al studied the kidney function of 54 transplanted patients (kidney, kidney-pancreas) after various graft-unrelated surgical procedures and concluded that kidney function remained stable in all patients [13] and Rivas et al reported no renal complications after laparoscopic colectomy of three transplanted patients [14]. Nyame et al reported the case of one patient after kidney-pancreas-transplantation, who underwent anterior pelvic exenteration without perioperative renal complications [15].…”
Section: Discussionmentioning
confidence: 99%
“…Only one case series of laparoscopic-assisted colectomy in three kidney transplant recipients has been published [ 19 ]. In that series, the average time since transplantation was 8 (range 6–10) years and no patient experienced organ rejection.…”
Section: Discussionmentioning
confidence: 99%